Speculating on precarious income: finance cultures and the risky strategies of healthy volunteers in clinical drug trials. Issue 4 (4th July 2021) - Fisher, Jill A.; Wood, Megan M.; Monahan, Torin
ABSTRACT: Speculation has become a normalized occupational strategy and quotidian economic rationality that extends throughout society. Although there are many contemporary articulations of speculation, this article focuses on contract labor as a domain of financialization. Seen through this lens, contract labor can be understood as a speculative investment strategy wherein individuals leverage whatever assets they have at their disposal – savings, time, bodily health – to capture economic advantages. In particular, we explore the speculative practices of healthy individuals who enroll in pharmaceutical drug trials as their primary or critical source of income. Mobilizing speculative logics to maximize the money they can earn from their clinical trial participation, these contract workers employ what we term a future-income-over-immediate-pay calculus . This speculative calculus valorizes fictional projections of significant long-term future income over present financial opportunities. For the economically precarious individuals in our study, we argue that rather than effectively increasing their income, speculation on contract work serves a compensatory function, providing an important – but ultimately inadequate – sense of control over market conditions that thrive upon workers' economic insecurity.